2018
DOI: 10.1590/s0004-2803.201800000-85
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and Clinical Outcomes in Surgical Patients With Colorectal Disease

Abstract: BACKGROUND: Malnutrition is a frequent condition among hospitalized patients and a factor of increased risk of postoperative complication. OBJECTIVE: This study aimed to evaluate the impact of malnutrition on phase angle (PA), body water distribution and clinical outcomes in surgical patients with colorectal disease. METHODS: This retrospective study was performed in a tertiary hospital with 40 patients admitted electively. In the preoperative evaluation, global subjective assessment and bioelectrical imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Accumulation of these changes and cell damage leads to apoptosis, which subsequently causes decreased muscle strength, gait instability, falls, fractures, respiratory infections, confusion, renal failure, increased medication toxicity, and an increased risk of death (25,28,29). Based on previous studies that have indicated an association between a high ECW/TBW and postoperative complications, such as infection (30,31), we hypothesized that a high ECW/TBW might predict poor clinical outcomes after treatment for advanced lung cancer, and our findings appear to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of these changes and cell damage leads to apoptosis, which subsequently causes decreased muscle strength, gait instability, falls, fractures, respiratory infections, confusion, renal failure, increased medication toxicity, and an increased risk of death (25,28,29). Based on previous studies that have indicated an association between a high ECW/TBW and postoperative complications, such as infection (30,31), we hypothesized that a high ECW/TBW might predict poor clinical outcomes after treatment for advanced lung cancer, and our findings appear to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition is associated with a worse prognosis, the presence of complications and a reduced response to treatment, in addition to increasing the length of hospital stay and being an independent factor for shorter survival [4][5][6]. Anorexia is often observed, along with a rapid loss of adipose tissue, tissue loss, and skeletal muscle atrophy [7], which may or may not progress to cachexia [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, with specific attention to vitamin D, it is possible to identify many other factors affecting vitamin D serum levels; some of them are linked with the environment, such as the season or the latitude, while others correlate with some specific patient characteristics, like age, gender or anthropometric values [37,38]. In the specific case of IBD, analyzing vitamin D levels while taking environmental factors into consideration reveals in many studies that vitamin D levels are higher in summer than in winter, and that the incidence of hypovitaminosis D is higher in the Northern than in the Southern population [1,2,21,27,39,40].…”
Section: Introductionmentioning
confidence: 99%